1977
DOI: 10.1063/1.89249
|View full text |Cite
|
Sign up to set email alerts
|

A new acceptor level in indium-doped silicon

Abstract: A new acceptor level located 0.111±0.002 eV from the valence band with a peak photoionization cross section of (1.4±0.6) ×10−16 cm2 has been observed in indium-doped silicon. Its presence is revealed both by the low-temperature slope of Hall measurements versus temperature and by the spectral response of the photoconductivity. The concentration of this 0.111-eV level is strongly correlated with the concentration of indium, suggesting that an In complex is responsible for this center.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
18
1

Year Published

1978
1978
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(24 citation statements)
references
References 9 publications
3
18
1
Order By: Relevance
“…8 meV observed for the shallower indium defect agrees with the value of ill ± 2 meV determined by Baron et al , ( 17) indicating that it is the same defect they observed. Also, the 56.3 meV observed for the sha llower aluminum defect agrees with the thermal activation energy often measured for aluminum , indicating t hat this shallower defect can dominate the electrical transport measurements under certain cir cumstance~.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…8 meV observed for the shallower indium defect agrees with the value of ill ± 2 meV determined by Baron et al , ( 17) indicating that it is the same defect they observed. Also, the 56.3 meV observed for the sha llower aluminum defect agrees with the thermal activation energy often measured for aluminum , indicating t hat this shallower defect can dominate the electrical transport measurements under certain cir cumstance~.…”
supporting
confidence: 81%
“…At the present time we have not been able to determine the origin of this shallow center. The work of Baron et al (8) suggests that this defect is not related to oxygen since it was observed in vacuum float-zoned crystals. In our crysta ls the indium concentration , the indium:X concentration and the oxygen concentration are all increasing wit h growth temperature , so oxygen cannot be ruled out on the basis of our work.…”
Section: Origin Of the Indium:x Defectmentioning
confidence: 98%
“…This energy is significantly lower than that of substitutional In in a Si matrix ͑0.156 eV͒. 14 Baron et al 15 attributed this acceptor level to a substitutional carbonsubstitutional indium (C S ϪIn S ) pair defect.…”
Section: ͓S0021-8979͑99͒06622-0͔mentioning
confidence: 99%
“…In ϩ was implanted in wafers I and II, with a dose of 5ϫ10 14 cm Ϫ2 at 50 keV. Both implantations were performed at room temperature ͑RT͒.…”
mentioning
confidence: 99%
“…In comparison, the acceptor level of boron lies at 0.048 eV, whereas after carbon co-implantation, the acceptor level of In-C pairs is 0.111 eV [7]. Experimental evidence demonstrates that the enhanced activation associated with the acceptor level in the bandgap is linked to a substitutional carbon-substitutional indium pair C8.4.2 [7]. For evaluation of activation a computational procedure similar to that used in Aronowitz et al is adopted [8].…”
Section: Methodsmentioning
confidence: 99%